Macro- and micro-morphologies and conservation status of Hymenorchis javanica (Orchidaceae: Aeridinae): the only representative of the genus in Malaysia - Besi, Edward Entalai; Nordin, Farah Alia; Go, Rusea (Firenze University Press, 2020)
Analysis of morphological characters and conservation status were carried out for Hymenorchis javanica from Peninsular Malaysia. Morphology was studied in detail and accompanied by a botanical drawing prior to the correct identification. From most closely related Hymenorchis phitamii found in Vietnam, it differs in the lip ovate-oblong with apex acute and margins entire, and the leaves margins prominently serrulate. Based on the current IUCN criteria, we proposed H. javanica as an endangered species under the threatened category. Judging from the current small population sizes and degraded habitats, H. javanica in Malaysia is threatened by extinction in the wild.